PRAKTIKALIAS PENGEMBANGAN PANDUAN PRAKTIKUM BERBASIS KETERAMPILAN PROSES SAINS PADA MATA KULIAH PRAKTIKUM IPA SD - Sari, Prima Mutia; Zulfadewina (Prosiding Seminar Nasional Berseri, 2020)
The aim of the research was to produce a science practicum guide for elementary school based on science process skill which was valid and practical. This practicum guide could be use in Elementary School Science Practicum subject. This research was research and development (R&D) with Hannafin and Peck model. There were some stage of this research: need assessment, design, and development/implementation. There were evaluation and revision in each of the stage. This development research was limited to the implementation stage. The need assessment, design and development stage has been carried out in previous research. Data collected technique was questionnaire to determine the response of lecturers and students. The Likert scale was used for the data and it was analyzed using qualitative descriptive statistics. The results of the lecturer response questionnaire stated that the practicum guides were very practical with an average rating of 90.3 and the results of the student questionnaire responses stated the practical practicum guides with an average rating of 81.05 on aspects of quality, understanding, science process skills, materials and languages